Reproducibility of Flow Cytometry Through Standardization: Opportunities and Challenges - Kalina, Tomas (Cytometry. Part A, 2020)
There is an agreement in the field that interlaboratory reproducibility of flow cytometry measurements as well as the whole studies might be improved by a consensual use of methodological approach. Typically, a consensus is made on a crucial markers needed in the immunostaining panel, sometimes on the particular fluorochrome conjugates and rarely on a complete set of methods for sample preparation. The term "standardization" is used to describe the complete set of methodical steps, while "harmonization" is used for partial agreement on the method. Standardization can provide a platform for improved reproducibility of cytometry results over prolonged periods of time, across different sites and across different instruments. For the purpose of structured discussion, several desired aims are described: common interpretation of the immunophenotype definition of a target subset, accurate quantification, reproducible pattern of a multicolor immunophenotype, and reproducible intensity of all measured parameters. An overview of how standardization was approached by several large consortia is provided: EuroFlow, The ONE Study, Human Immunology Project Consortium (HIPC), and several other groups. Their particular aims and the tools adopted to reach those aims are noted. How those standardization efforts were adopted in the field and how the resulting outcome was evaluated is reviewed. Multiple challenges in the instrument hardware design, instrument setup tools, reagent design, and quality features need to be addressed to achieve optimal standardization. Furthermore, the aims of different studies vary, and thus, the reasonable requirements for standardization differ. A framework of reference for the reasonable outcomes of different approaches is offered. Finally, it is argued that complete standardization is important not only for the reproducibility of measurements but also for education, for quality assessment and for algorithmic data analysis. The different standardized approaches can and in fact should serve as benchmarking reference tools for the development of future flow cytometry studies. © 2019 International Society for Advancement of Cytometry.
Keywords: Humans; referenční standardy; data analysis; Reference Standards; Reproducibility of Results; flow cytometry; EuroFlow; reprodukovatelnost výsledků; Immunophenotyping; indikátory a reagencie; Flow Cytometry; Indicators and Reagents; standardization; lidé; průtoková cytometrie; imunofenotypizace